2016
DOI: 10.3390/nu8110681
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Nutritional Antioxidant Content in Breast Milk, Donor Milk, and Infant Formulas

Abstract: Human milk is the optimal food for human infants, including infants born prematurely. In the event that a mother of a hospitalized infant cannot provide breast milk, donor milk is considered an acceptable alternative. It is known that the macronutrient composition of donor milk is different than human milk, with variable fat content and protein content. However, much less is known about the micronutrient content of donor milk, including nutritional antioxidants. Samples of breast milk from 12 mothers of infant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 47 publications
0
46
0
1
Order By: Relevance
“…Studies have shown that an important cause of BPD is oxidative stress, which may be due to mechanical ventilation, infection and other causes 42. Early cumulative supplemental oxygen exposure is independently associated with BPD 45.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that an important cause of BPD is oxidative stress, which may be due to mechanical ventilation, infection and other causes 42. Early cumulative supplemental oxygen exposure is independently associated with BPD 45.…”
Section: Discussionmentioning
confidence: 99%
“…This pattern of abundance for non-α-tocopherols is also evident in 29 species of beans, in which γ-tocopherol and δ-tocopherol were the most abundant isomers, with only a discrete amount of α-tocopherol [7]. Interestingly, δ-tocopherol has also been detected in human milk (2.8 µM) [8][9][10]. Therefore, it is clear that early in life during breastfeeding or from the diet in adulthood, we are exposed not only to α-tocopherol but to all the isomers.…”
Section: Introductionmentioning
confidence: 68%
“…Although evidence exists regarding the protective effects of MOM in reducing the risk of necrotizing enterocolitis (NEC), late-onset sepsis (LOS), and retinopathy of prematurity (ROP) in VLBW infants, questions remain regarding whether DHM provides the same benefits [5,[8][9][10][11][12][13][14]. Numerous MOM components which could contribute to protect against adverse outcomes of prematurity are reduced or absent in DHM which is usually pasteurized [14][15][16].…”
Section: Introductionmentioning
confidence: 99%